Climatic impact on atmospheric turbidity at some Indian stations (MAUSAM, 1997)
Data from four Indian BAPMoN stations in different climatic regions were analysed using principal component analysis (PCA) for the evaluation of climatic impact upon turbidity.  Spectral analysis (FFT) of the data for these stations has helped to bring out the sub-seasonal, seasonal and annual cycles. It is found that the atmospheric turbidity is predominantly controlled by climatic factors through surface fluxes, transport of dust or rain washout and is mainly a lower tropospheric phenomenon. The performance of the PCA regression model is found satisfactorily in reproducing the annual cycle and long period variations.